Empowering Community Legal Awareness in The Utilization of Mining Natural Resources and Environmental Protection - Ilyas; Ichsan, Nursyamsi; Nasir, Citra; Hasmiati Attas, Nasrah; Eka Saputra, Tri (Journal of Indonesian Scholars for Social Research, 2022)
The problem phenomenon is that people in various regions (provinces, districts/cities, sub-districts, villages/sub-districts) tend to still face legal awareness problems, especially in the use of natural resources (SDA) for matters and interests of mining business and investment activities. This is characterized by a low lack of legal knowledge and understanding, especially regarding the regulatory provisions regulated in the Mineral and Coal Mining Law No.3 of 2020 and the PPLH Law No.32 of 2009. As a result of this situation and condition, many community members do not have a legal attitude and clear patterns of legal behavior, are unable to differentiate between acts and actions that are permitted and prohibited in the use of natural resources, and do not know the rights and obligations and responsibilities in managing mining businesses, and not knowing the categories of administrative and criminal violations and others. This training aims to determine the level of legal awareness of the community before carrying out activities in Mosiku Village, Batu Putih District, and North Kolaka Regency and to build a joint commitment to empowering legal awareness in using mining natural resources and environmental protection. The output of this activity is the availability of a model for empowering community legal awareness in the utilization of mining natural resources and environmental protection.